(untitled) - Morgan, Michael (Indianapolis, IN, 1996)
Demonstrating how to build and maintain Web sights as well as add network- and enterprise-wide database connectivity, a guide for Java programmers covers LiveWire, Netscape Scripting, Navigator Gold 2.0, and more. Original. (Advanced)
Keywords: Netscape LiveWire (tệp tin máy tính),Netscape LiveWire (Computer file)